2020
DOI: 10.1177/1747954120942051
|View full text |Cite
|
Sign up to set email alerts
|

The creation of goal scoring opportunities at the 2015 women’s world cup

Abstract: Women’s international football is growing in terms of popularity, but to date there is limited published research in women’s football and even less that describes effective attacking strategies and the creation of goal scoring opportunities (GSO). The purpose of this research was to investigate and assess the factors related to the creation of GSO that led to a Top 4 position Canada Women’s World Cup 2015. Video footage of each match (n = 52) from the Women’s World Cup (Canada 2015) was analysed using SportsCo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 11 publications
1
24
0
3
Order By: Relevance
“…On the other hand, the nearer to the rival goal is the start of the offensive action, the greater the probability of success in ball possessions. This was the very conclusion that Scanlan et al [21] came to after analysing the creation of goal opportunities in the FIFA Women's World Cup Canada 2015. These results agree with the existing bibliography on men's elite soccer in which there is great consensus concerning the influence of these criteria on the success of possessions [19,20,22,25,26].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…On the other hand, the nearer to the rival goal is the start of the offensive action, the greater the probability of success in ball possessions. This was the very conclusion that Scanlan et al [21] came to after analysing the creation of goal opportunities in the FIFA Women's World Cup Canada 2015. These results agree with the existing bibliography on men's elite soccer in which there is great consensus concerning the influence of these criteria on the success of possessions [19,20,22,25,26].…”
Section: Discussionmentioning
confidence: 95%
“…In women's soccer, it was also seen that this was a variable that modified ball possession following analysis of the FIFA Women's World Cup Canada 2015 [18]. The kind of start of possession and the zone in which it was produced proved to be tactical indicators significantly linked to success in men's soccer [19,20] and in women's soccer [21]. It was also shown that once possession of the ball was recovered, the offensive tactical intention [22] significantly modified the development of offensive actions in men's soccer: the teams that showed a tactical intention to move quickly towards the rival goal had a greater probability of finishing their offensive actions successfully.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Kirkendall and Urbaniak [ 38 ], only 25% of football-related publications focus on women’s football. Some of the studies published on tactical aspects [ 39 , 40 , 41 ] focus on the differences between both types of football. Specifically, it was shown that the duration of the attack, as well such as the starting area of this, were significant criteria when evaluating the probability of obtaining offensive success by the teams analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…En relación con estos criterios, varias publicaciones han analizado el desarrollo y resultado de las posesiones de balón en fútbol femenino en la Copa Mundial Femenina de la FIFA de Canadá 2015. Scanlan et al (2020) analizaron qué criterios determinaban la consecución de oportunidades de gol, encontrando que las posesiones de balón que daban comienzo mediante un robo a una interceptación, finalizaban en mayor medida en una oportunidad de gol. Por otro lado, un estudio presentado por Maneiro et al (2021) demostró que existía una asociación significativa entre el éxito ofensivo en las posesiones de balón y los criterios: i) temporalidad: se observó una mayor probabilidad de que las acciones ofensivas finalizaran con éxito en las segundas partes (p<.001); ii) intención inicial ofensiva: las posesiones que daban comienzo mediante una intención de progresar rápidamente finalizaron con éxito en mayor medida (p<.001); iii) tiempo de posesión (p<.001) y iv) número de pases (p<.001).…”
Section: Introductionunclassified